Effect of a community-based multicomponent intervention on cervical cancer behavior among women - A randomized controlled trial - T Jisa George; Kiran Batra (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: Cervical cancer is the leading cause of death worldwide, especially in developing countries. More than one-fifth of newly diagnosed cervical cancer cases are occurring in India. Cervical cancer is a highly preventable and curable cancer compared with other types of cancer, if detected at an early stage. The present study has been carried out to assess whether a community-based, multicomponent, nurse-led intervention program improves cervical cancer screening behavior of women. MATERIALS AND METHODS: An experimental randomized controlled trial was carried out by recruiting 419 women in the age group of 30-60 years (246 in the experimental group and 173 in the control group) residing in a selected rural community (selected tribal settlements) of Idukki district of Kerala, India, using multistage cluster sampling. The intervention comprising small group education followed by reinforcement session, telephonic reminders, navigation and guidance for Pap smear, and follow-up visit by the investigator was administered to the experimental group, and the control group did not receive any intervention. Knowledge, attitude, and screening behavior of women related to prevention of cervical cancer were assessed before and twice after the intervention. RESULTS: The experimental and control groups were homogenous in all baseline sociodemographic variables. The community-based intervention program was effective in improving knowledge (P < 0.001), attitude (P < 0.001), and screening behavior (P < 0.001) of women regarding the prevention of cervical cancer. A significant moderate positive correlation was found between knowledge and screening behavior (r = 0.408). Significant association was found between knowledge, attitude, and practice regarding prevention of cervical cancer with education, age at the time of marriage, and number of pregnancies. CONCLUSION: The community-based, multicomponent, nurse-led intervention program was effective in improving cervical cancer screening behavior among women. Repeated motivation and reinforcement are needed to bring behavioral change and to increase uptake of screening services among rural women.